Development of a New Container for Storage and Release of the Parasitoid Cotesia flavipes (Hymenoptera: Braconidae) - Santos, Rafael F. dos [UNESP]; Vacari, Alessandra M. [UNESP]; Bortoli, Sergio A. de [UNESP]; Bortoli, Caroline P. de [UNESP]; Santos, Josy A. (Oxford Univ Press Inc, 2015)
In Brazil, the parasitoid Cotesia flavipes (Cameron) has been used as a biological control agent against Diatraea saccharalis (F.) since 1976, because of its effectiveness in reducing populations of this pest. Three million plastic cups are used annually to release C. flavipes, which remain in the environment. This study aimed to develop fully biodegradable packaging, so that releases occur without damaging the environment. The biological characteristics of C. flavipes were studied for five generations in the packaging developed (biodegradable boxes) and in the packaging currently used (non-biodegradable plastic cups and biodegradable cups), as were the costs. The results demonstrated the feasibility of using completely biodegradable and inexpensive packaging for the rearing, transport, and release of adult C. flavipes in the field.
Keywords: biological control; mass-rearing; insect biology